Linking Work-Life Balance And Work Engagement To Performance: The Role Of Organizational Commitment As A Moderator - Irpan (PT PUSTAKA CENDEKIA GROUP, 2025)
This study examines the influence of work-life balance and work engagement on performance in personnel of the South Sulawesi Police Directorate of Criminal Investigations, and assesses the role of organizational commitment as a moderation variable in this relationship. The researcher used a quantitative approach with an explanatory design and collected data from one hundred and twenty respondents who were selected according to the research criteria. The researcher analyzed the data using SEM PLS because this method tests the relationships between latent variables simultaneously, reads the direct and indirect influences, and supports testing the role of moderation in a single model. The researcher conducts an analysis through SmartPLS with the evaluation stage of the measurement model to ensure the indicators are valid and reliable, then the evaluation of the structural model to test the strength of the relationship and the significance of the path. The results of the study show that work-life balance has a positive and significant effect on performance, so that the balance of work time and personal time plays a role in maintaining focus, work resilience, and the quality of task completion. Work engagement also has a positive and significant effect on performance, with a stronger influence than work-life balance, so that work attachment is the main driver of performance improvement. Moderation testing shows that organizational commitment strengthens the relationship between work-life balance and performance, so that the impact of work-life balance is greater when organizational commitment is high. In contrast, organizational commitment does not moderate the relationship between work engagement and performance, so increasing work attachment still encourages consistent performance at different levels of commitment.